Effect of DNA template concentration on standard polymerase chain reaction / Alif Haikal Mazlan ... [et al.] - Mazlan, Alif Haikal; Muhamad Najib, Muhamad Hafizal Aqhmal; Hazizul Hassan, Mizaton; Mohd Hatta, Fazleen Haslinda; Mohd Yusoff, Rosmadi (Faculty of Pharmacy, 2024)
The polymerase chain reaction (PCR) was an essential fundamental procedure widely used in molecular biology to amplify specific deoxyribonucleic acid (DNA) sequences. To investigate the efficiency and specificity of PCR using DNA extracted from human blood cells as sample, several concentrations of DNA templates were used to obtain accurate and reproducible results during this optimisation process. The principal objective was to identify which concentration was the best for amplifying the DNA target sequence and study the effects of the scale of concentrations to standard PCR. For this study, a series of PCR were conducted using various concentrations of DNA template ranging from 1 ng/μL to 100 ng/μL per reaction under optimized conditions of primer concentrations, annealing temperature and extension time. The results demonstrated that DNA template concentration significantly influenced the efficiency and specificity of PCR as the intensity of the target gene amplification band was increased on the agarose gel electrophoresis under ultraviolet light indicating the PCR product yield. Formation of primer-dimers became more prominent as the DNA template concentration reduced resulting in non-specific amplification. The concentrations ranging from 10 ng/µL to 70 ng/µL were the most optimal reactions profiting a remarkable feat of target gene amplification while concentrations less than 1 ng/µL produced none and non-specific outcomes retaining little amount of target gene amplification. In conclusion, our study highlights the pivotal role of DNA template concentration optimises PCR to increase reliability and reproducibility, extending our understanding of genetic analysis, diagnostic, and forensic sciences.